Enantiosemy: Unity or Struggle of Opposites? - Yuriy Murzin (Ибероамериканские тетради, 2018)
The phenomenon of enantiosemy is due to the semantic evolution of the word has resulted in the formation of an opposite meaning to the main meaning of the same. Are key elements of this process, the dualism of human thinking, the asymmetry of the linguistic sign, the meaning diffuse the root of the etymon and the inversion of the relation subject-object, among others. Sometimes, as a result of the diachronic variation of the nuclear meaning the word lose in a certain period of time its original meaning which recur with time in some phrases or syntactical constructions which form the word.The lexical-semantic variants of a word count with nuclear common semes. Are opposed to them generally non-nuclear semes. The meaning of the enantiosemic word only you can reveal it from the context. The opposite meanings present a case of polysemy and form a single whole. The concepts that these words are complemented to designate objects, processes or phenomena, simultaneous or consecutive inextricably linked to each other.In the present work, we analyze cases of nominative, grammatical and conversive enantiosemy of some nouns, pronouns, adverbs and verbs. The study was carried out on the basis of lexicographical, literary and journalistic examples.